Active vibration control of a mechanical servo high-speed fine-blanking press - Liu, Yanxiong (Strojniški vestnik, 2021)
The fine-blanking process as an advanced sheet metal forming process has been widely applied in industry. However, specially designed equipment is required for this process. In this paper, a novel mechanical servo high-speed fine-blanking press with the capacity of 3200 kN is proposed, and the vibration control for this machine is researched to achieve the requirement of fine-blanked parts of high dimensional accuracy, since the vibration of the fine-blanking machine will cause the machining displacement error and reduce the machining accuracy. Self-adaptive feed-forward control is used to simulate the active vibration control of the mechanical fine-blanking machine. The vibration control principle of the fine-blanking machine is described, and the control algorithm is established. At the same time, the mechanical vibration model of the fine-blanking machine as the controlled object is established, and the parameters of the excitation input and the mechanical model are obtained by the fine-blanking finite element simulation and the experiments of the vibration measurement of the press. Finally, the numerical simulation and analysis of active vibration control based on MATLAB are carried out. The results show that the control effect is good, and the vibration response is effectively reduced, thus greatly increasing the processing accuracy, saving a significant amount of energy, and reducing the energy consumption and defective rate.
Keywords: active vibration control; aktivni nadzor vibracij; mechanical servo high-speed fine-blanking presses; mechanical vibration model; mehanski model vibracij; samoadaptivno krmiljenje; self-adaptive feed-forward control; visokohitrostne mehanske servostiskalnice